Pendampingan Digital Marketing pada Pelaku UMKM di Pasar Desa Bulusari Kecamatan Gempol Kabupaten Pasuruan - subchan asy'ari (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
The development of information technology that is developing rapidly now influences the community in supporting a variety of large and small business activities so that it can be recognized globally. The most obvious impact is that besides being known, it can also increase sales volume and profit and help MSMEs determine sales strategies with the concept of Digital Marketing. In digital marketing activities, there are several positive and negative impacts. If seen from real activities, there are many positive impacts mentioned that can increase the sales volume of MSMEs, facilitate sales access, become more effective and efficient in daily economic activities. The negative impacts often found in the field are prone to fraud and cause concern in the community. This program aims to provide literacy to the public about the concept of digital marketing and also the dissemination of how to apply and the stages of digital marketing properly to avoid negative impacts. This program will provide literacy in the form of workshops and video screenings on digital marketing and outreach to MSMEs of Bulusari village, whether they conduct sales transactions digitally. It is hoped that MSMEs in the village of Bulusari can have a good understanding of implementing digital marketing at the time of the sales transaction and avoid the adverse effects of digital ordering. So through digital marketing, the community can run the economy, especially the Bulusari village community.